Pengembangan Aplikasi Funmath Terhadap Kemampuan Berpikir Kritis Siswa pada Materi Eksponen Kelas X (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to develop the application of FunMath to students' critical thinking skills in exponential material in class X. This research uses a type of development research. In this study, the ADDIE development model is used. The subjects of this product trial research are students and students of MAN 1 Pontianak Class X I. The stages in this study are analysis, design, evelopment, implementation, and evaluation. The data collection technique used in this study is in the form of a questionnaire to see the practicality of the application and a validation sheet to see the validity of the application. The instruments used in this study include, validation sheets for media experts and material experts, validation sheets for teacher and student response questionnaires, teacher response questionnaires and student response questionnaires, and tests for students' critical thinking skills. The data analysis techniques used in answering the sub-sub-problems in this study are validity, practicality, and effectiveness. The results of the study showed that there was an increase in mathematical comprehension ability from the calculation results obtained tcal>ttable = 4.86 >2.07, thus Ho was rejected Ha was accepted, after the application of the FunMath application which can affect critical thinking skills.